Atomic collision cascades on void evolution in vanadium - Xu, S. Z.; Hao, Z. M.; Su, Y. Q.; Hu, W. J.; Yu, Y.; Wan, Q. (Radiation effects and defects in solids, 2012)
Molecular dynamics simulations were performed to study void evolution subject to unidirectional self-bombardment and radiation-induced variation of mechanical properties in single crystalline vanadium. 3D simulation cells of perfect body-centered cubic (BCC) vanadium, as well as those with one, two, four, and six voids, were investigated. For the no void case, the maximum number of defects, maximum volumetric swelling, and the number of defects left in bulk after a sufficiently long recovery period increased with higher primary recoil energy. For the cases containing voids, a primary recoil energy was carefully assigned to an atom so as to initiate a dense collision spike in the voids center, where some self-interstitial atoms gained kinetic energy by secondary replacement collision sequence traveling along the ⟨ 111⟩ direction. It is found that the larger or the greater the number of voids contained initially in the box, the larger the normalized void volume, and the smaller the volumetric swelling after sufficient recovery of systems. In the single void case, the void became elongated along the bombarding direction; in the multiple void cases, the voids coalesced only when the intervoid ligament distance was short. After sufficient relaxation of the irradiated specimen, a hydrostatic tension was exerted on the box, where the voids were treated as dislocation sources. It is shown that with higher primary recoil energy, the yield stress dropped in cases with smaller or fewer voids but rose in those with larger or greater number of voids. This radiation-induced softening to hardening transition with increasing dislocation density can be attributed to the combined effects of the defect-induced dislocation nucleation and the resistance of defects to dislocation motion. Moreover, as the primary recoil energy increased, the ductility of vanadium in the no void case decreased, but was only slightly changed in the cases containing void.